3d–4f heterometallic complexes by the reduction of transition metal carbonyls with bulky LnII amidinates. Issue 23 (12th May 2020) - Yadav, Ravi; Hossain, Md Elius; Peedika Paramban, Ramees; Simler, Thomas; Schoo, Christoph; Wang, Jun; Deacon, Glen B.; Junk, Peter C.; Roesky, Peter W.
Abstract : Heterometallic lanthanide-transition metal carbonyl complexes [Sm2 –Co2 ], [Yb–Co], and [Sm2 –Fe3 ] have been synthesized by redox reactions between bulky amidinate stabilized divalent Ln and TM carbonyl complexes. Abstract : The redox chemistry between divalent lanthanide complexes bearing bulky amidinate ligands has been studied with 3d transition metal carbonyl complexes (iron and cobalt). The reaction of [(DippForm)2 Sm II (thf)2 ] (DippForm = N, N ′-bis(2, 6-diisopropylphenyl)formamidinate) with [Co2 (CO)8 ] resulted in the formation of a tetranuclear Sm–Co complex, [{(DippForm)2 Sm III (thf)}2 {(μ-CO)2 Co(CO)2 }2 ]. The product of the reaction of [(DippForm)2 Yb II (thf)2 ] and [Co2 (CO)8 ] gives the dinuclear Yb–Co complex [{(DippForm)2 Yb III (thf)}{(μ-CO)Co(CO)3 }] in toluene. The reaction of [(DippForm)2 Sm II (thf)2 ] was also carried with the neighbouring group 8 carbonyl complexes [Fe2 (CO)9 ] and [Fe3 (CO)12 ], resulting in a pentanuclear Sm III –Fe complex, [{(DippForm)2 Sm III }2 {(μ3 -CO)2 Fe3 (CO)9 }], featuring a triangular iron carbonyl cluster core.